131k views
4 votes
Solve the following equation by factoring. Separate multiple answers with a comma x^3 - 10x = 3x^2

User Shmichael
by
5.3k points

1 Answer

1 vote

Given the equation:


x^3-10x=3x^2

We will solve the equation by factoring as follows:

Make all terms on the left side of the equations:


x^3-3x^2-10x=0

Take x as a common factor from all terms:


x(x^2-3x-10)=0

Factor the equation:


x(x-5)(x+2)=0

Solve:


\begin{gathered} x=0 \\ \\ (x-5)=0\rightarrow x=5 \\ \\ (x+2)=0\rightarrow x=-2 \end{gathered}

so, the answer will be x = { -2, 0 , 5 }

User Sanchitos
by
5.2k points